2022
DOI: 10.3390/antibiotics12010027
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Potential of Metabolites in Fungal Strains Isolated from a Polluted Stream: Annulohypoxylon stygium WL1B5 Produces Metabolites against Extended-Spectrum Beta-Lactamase-Positive Escherichia coli

Abstract: The emergence of multidrug resistance in bacterial pathogens is a growing public health concern requiring solutions including the discovery of new antimicrobial drugs. Fungi have been used for decades as a source of antimicrobials. Ongoing screenings for newly characterized fungal strains producing antimicrobials include environments that are difficult to access like the deep sea, glaciers, wastewaters and environments polluted due to human activity. In the present study, fungal microorganisms were isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Fungi, specifically species such as Penicillium Link, Cephalosporium Corda, Acremonium Link, and Fusarium Link, have enabled the discovery of antimicrobial substances like penicillins, cephalosporins, and fusidic acid (Ajah et al, 2018;Newaz et al, 2023;Farhat et al, 2019;Nelsonjoseph et al, 2022). To discover new fungal metabolites for use as antimicrobials, researchers have been motivated to isolate fungal strains from environments such as the bottom of the sea, animal intestines, and extreme environments (Segundo et al, 2022;Adebayo et al, 2021). Previous research has shown that freshwater fungi have the potential to produce metabolites that possess antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Fungi, specifically species such as Penicillium Link, Cephalosporium Corda, Acremonium Link, and Fusarium Link, have enabled the discovery of antimicrobial substances like penicillins, cephalosporins, and fusidic acid (Ajah et al, 2018;Newaz et al, 2023;Farhat et al, 2019;Nelsonjoseph et al, 2022). To discover new fungal metabolites for use as antimicrobials, researchers have been motivated to isolate fungal strains from environments such as the bottom of the sea, animal intestines, and extreme environments (Segundo et al, 2022;Adebayo et al, 2021). Previous research has shown that freshwater fungi have the potential to produce metabolites that possess antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%